Factors Associated with Enrollment of Household in National Health Insurance Program in Eastern Nepal - Timsina, Koshika; Silwal, Suvekshya; Mandal, Punam Kumari; Basnet, Saraswati (Journal of College of Medical Sciences-Nepal, 2024)
Background Health insurance is entrusted to make health services more equitable and decrease the financial burden caused by catastrophic out-of-pocket payments. This study aimed to assess the factors affecting the enrollment of households in National Health Insurance Program (NHIP) in eastern Nepal. Methods Cross-sectional data were collected from 189 households in Itahari sub-metropolitan city using a structured questionnaire. Chi-square tests was used to examine the association between NHIP enrollment and selected demographic variables derived from the data. Results The findings showed that 63% of households were enrolled in NHIP and enrollment was associated with education, family type, ethnicity, socio-economic status, prior experience of illness, utilization of health facilities, and knowledge regarding NHIP. Conclusions Variables like education, family type, ethnicity, socio-economic status, prior experience of illness, utilization of health facility, knowledge regarding the annual premium amount, annual benefit ceiling, and renewal time found to be associated with NHIP enrollment.